The Influence of Product Design and Promotion on Purchase Decisions of Terune Apparel Distro Products in Selong District: Pengaruh Desain Produk dan Promosi terhadap Keputusan Pembelian Produk Distro Apparel Terune di Kecamatan Selong - Cahyani Yuyun izza cahyani; Rahman Dayani; Dwi Putra Buana (Institut Studi Islam Sunan Doe, 2023)
The development of fashion and fashion in the international world has caused many demands in society to update fashion constantly. The magnitude of this fashion demand causes competition among clothing manufacturers. This research examined the influence of product design and promotion on purchasing decisions for distro Terune apparel products in the Selong sub-district. the purpose of this study was to determine the effect of the influence of product design and promotion on product purchase decisions in terune apparel distro in seong district. This study uses a quantitative-explanative method with the data source from this study, namely consumers who use terune apparel distro in seong district. The results of this study indicate that product design and promotion variables influence respondents' purchasing decisions with positive and significant results. The implications of this research provide input so that the Terune apparel Distro can maintain and continue to improve its product design and promotion, as well as continue to make improvements and innovations so as not to be left behind by competitors.